History of the use of system method in research of properties of criminality - Оболенцев, В. Ф. (Problems of legality, 2013)
The article is devoted history of system method in criminology. Maintenance of criminology theories, offered the Ukrainian scientists is exposed. Perspective of the use of system method in criminology researches is grounded.